(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
One of the ’vital signs’ or essential health markers of the human body, is the rate of the heart or pulse. It tracks the time the heart beats or pumps every minute. Generally, a lower rating (LR) suggests a greater efficiency of coronary activity, a higher rating of cardiac incidents like stroke and heart attacks, and study has associated higher rating of cardiac events. Sport forces the heart to pump enough blood into the lungs and muscles to satisfy demand and eventually learn to pump enough blood with less beats over a period of time. Flexibility workouts make good musculoskeletal base which helps to do the aerobic exercises like brisk walking, running, swimming etc. that strengthens the cardiac muscles and improve cardiac output. The more you exercise, the harder you train, the lower your resting heart rate which often cited as a good measure of how fit a person is.